Thermal and sound properties of concrete mixed with high porous aggregates from manufacturing waste impregnated with phase change material - Pattra Uthaichotirat (2020)
© 2019 Elsevier Ltd In this study, the properties of lightweight concrete manufactured from high porous aggregates impregnated with phase change material (PCM) were investigated. The aggregates used are in the form of waste retrieved from the manufacturing process of autoclaved aerated concrete block (ACC). The PCM (paraffin type) was used to impregnate the blocks at about 65% by weight. The non-PCM aggregates were replaced by PCM aggregates from 25 to 100% by volume. Five experiments were carried out: density and absorption (ASTM C138), compressive strength (EN12390), flexural strength (ASTM C78), thermal behavior, and sound transmission loss. Results showed increasing trends in density, compressive, and flexural strength with the increase PCM aggregate content. Thermal behavior is also found to improve with increasing PCM aggregates. Sound transmission loss, however, was found to decrease with increasing PCM aggregates.